Students’ Learning Interest: The Effectiveness of the Think Talk Write Learning Model - Amia Kasmila; Deden Makbuloh; Sunarto Sunarto; Saiful Bahri; Jalaluddin Jalaluddin (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
This research is conducted to investigate the effectiveness of using a Think-Talk-Write instructional Towards students' learning interest in the Islamic Religious Education subject at SMP Negeri 03 Bukit Kemuning, Lampung Utara. Employing a quantitative approach, this research utilizes an experimental method with a post-test only control group design. This Research Comprises two groups: a control class instructed through conventional teaching methods and an experimental class that implements The Think-Talk-Write model. The research instrument comprises a non-test questionnaire, with data collected through the distribution of validated and reliable item. The questionnaire was administered to students' learning following the instructional intervention. Data analysis Was carried out with an independent sample T-test to identify notable differences in students' learning interest among those presented to The Think-Talk-Write model and those who were not. The normality test results indicate that Information from both the experimental and control groups adheres to  normal distribution, as evidenced by a significance level of 0.60, which exceeds the threshold of 0.05. Additionally, homogeneity test confirms Indicating that the information exhibit homogeneity, Having a statistical significance value of 0.448, additionally surpassing 0.05. The outcomes of the T-test reveal a Sig. (2-Tailed) value of 0.000, which is significantly lower than 0.05. Based on these findings, it can be conclusively stated that the Think-Talk-Write instructional model proves to be more effective in fostering students’ learning interest compared to conventional teaching methodologies.